Perceptions of Women Undergoing Breast Cancer Treatment about the Impact of Belly Dancing on Optimism and Self-Esteem: MoveMama Study - Moschen, Lyara da Silva (2021)
Introduction: There is a growing profusion of studies attempting to relate gains brought by physical activity to the adjuvant treatment of breast cancer. Objective: To investigate perceptions of optimism and self-esteem of women undergoing hormone therapy adjunctive treatment for breast cancer after belly dance interventions. Method: Randomized descriptive and exploratory design mixed approach (quali-quantitative) clinical trial where 14 women aged 40 to 71 years were randomized to belly dance intervention group in hormone therapy adjuvant clinical treatment at the Oncological Research Center in a Brazilian southern city. A questionnaire applied as individual interview divided in three parts was used: a) socioeconomic variables; b) optimism and c) self-esteem. Systematic and participatory observations during the belly dance intervention were completed and logged in a field diary and reviewed through discourse analysis. Results: It was possible to see an increase in women’s self-esteem in the post-intervention period (p<0.001). On the other hand, for the five women who, in addition to finalizing the intervention, also participated of the interview (pre and post) the quantitative results have barely changed. The study shows a clinical improvement in optimism with standard deviation of 4.6 after the intervention, which can be interpreted as expressive, even though it has no statistical impact considering the use of a mixed methodology in the present study. Conclusion: Regarding self-esteem, women’s perceptions confirmed qualitatively and quantitatively in this study are positive, however, despite this, the confirmation of quantitative results for optimism was modest.